2013
DOI: 10.1186/1471-2369-14-137
|View full text |Cite
|
Sign up to set email alerts
|

Risk of human papillomavirus-related cancers among kidney transplant recipients and patients receiving chronic dialysis - an observational cohort study

Abstract: BackgroundIndividuals with end-stage renal disease (ESRD) have excess risk of various cancer types. However, the total burden of human papillomavirus-related cancers remains unknown.MethodsWe performed a nationwide observational cohort study during 1994–2010.For each person with ESRD, we sampled 19 population controls (without ESRD) matched on age, gender and municipality. Participants were followed until first diagnosis of human papillomavirus-related cancer, death, emigration, or 31 December 2010, whichever … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
6
23
0
1
Order By: Relevance
“…These results are in accordance with previous population‐based registry studies reporting an increased rate of cervical cancer and other HPV‐related anogenital cancers in RTRs compared to the general population. While most of the previous studies were based on calculation of standardized incidence ratios, we were able to adjust for potential confounders, including socioeconomic characteristics, HPV vaccination, HIV/AIDS and other solid organ transplants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are in accordance with previous population‐based registry studies reporting an increased rate of cervical cancer and other HPV‐related anogenital cancers in RTRs compared to the general population. While most of the previous studies were based on calculation of standardized incidence ratios, we were able to adjust for potential confounders, including socioeconomic characteristics, HPV vaccination, HIV/AIDS and other solid organ transplants.…”
Section: Discussionsupporting
confidence: 92%
“…Virtually all cervical cancers and approximately 80–90% of anal squamous cell carcinomas (SCCs), 70% of vaginal SCCs, 40% of vulvar SCCs and 50% of penile SCCs are estimated to be caused by HPV. Several large, population‐based registry studies have found that RTRs have an increased risk of HPV‐associated anogenital cancers compared to the general population . It has been hypothesized that the immunosuppressive treatments received by RTRs decrease their ability to clear newly acquired HPV infections and/or increase their risk of reactivation of latent HPV infections .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations